Quantity Content: Developing Mathematics PISA-Like Problems with Independence Day Contest Context - Fadlila, Nindy; Wijaya, Ariyadi; Hilmi, Irfan (Universitas Muhammadiyah Mataram, 2022)
PISA is an international scale assessment in which it measure mathematical literacy skills. Indonesia was one of the participants who took part in the PISA assessment. PISA results show that Indonesia is still at a low level. In fact, some study show that the ability of Indonesian students to solve PISA questions on the quantity content of students is not good and is still low compared to other content. This research aims to produce PISA-Like math questions with Quantity content that are valid, practical and have a potential effect on mathematical literacy skills. This research using a development research which consists of preliminary, self-evaluation, expert review, one-to-one, small group, and field test stages. The subjects in this study were students of class IX-4 SMP inone of the junior high schools in Medan. The results of this study are PISA-Like questions with Quantity content in valid and practical criteria. From the analysis of students’ answers regarding the potential effect involved in mathematical literacy, the results show that students involve communication skills, reasoning and argument skills, mathematical abilities, representation abilities, devising strategies for solving problems, and using symbolic, formal skill, and technical language and operations.